Health Literacy and Health Behavior in the Rural Areas - ., Nurjanah; Mubarokah, K (KnE Life Sciences, 2019)
Health literacy is a very important skill to navigate people doing health behavior and achieving good quality of life. People who live in rural area potentially have lower health literacy since they have limited access to health information and healthcare. the study aims to assess the health literacy and health behavior of family leader (father or mother) of limbangan residents. The was a survey with cross-sectional design conducted in November 2015 over 583 respondents, with HLS-EU-Q16 as an instrument. The chi-square test was used to analyze data. The most respondents having low health literacy, 19.2% of them had inadequate health literacy level, while 44.3% in problematic category and only 36,5% had sufficient health literacy. The health behavior factors related to health literacy were: toothbrushing (p value 0.004, PR 2.017), washing hand before eating (p value0.002, PR 2.175) and after defecation (p value0.002, PR 2.175). The people who had low health literacy turn out to be a smoker although it is not correlated significantly. Health literacy had an important role to health behavior that contributed to health status. The access of health information and healthcare should be improved. Keywords: Health literacy, health behavior